Evol2Circos: A Web-Based Tool for Genome Synteny and Collinearity Analysis and its Visualization in Fishes. (25th July 2020) - Pandey, Manmohan; Kushwaha, Basdeo; Kumar, Ravindra; Srivastava, Prachi; Saroj, Suman; Singh, Mahender
Abstract: The advent of high throughput next-generation sequencing technologies and improved assembly algorithms have resulted in the accumulation of voluminous genomic data in public domains. These technologies have opened up entries for large scale comparative genome studies, especially the identification of conserved syntenic blocks among species, facilitating studies of the evolutionary importance of the conservation and variation in genomic organization. Synteny construction and visualization require computational and bioinformatics skills to prepare input files for the synteny analysis pipeline. The syntenic information for fishes is still in a juvenile stage and is scattered among different research domains. Here, we present a web-based tool " Evol2Circos " to provide a user-friendly graphical user interface (GUI) to analyze user-specific data for synteny construction and visualization, and to facilitate the browsing of syntenic information of different fishes using the Circos, bar, dual, and dot plots. The information generated from the tool can also be used for further downstream analyses. Evol2Circos software tool is tested under Ubuntu Linux. The web-browser, source code, documentation, user manual, example dataset and scripts are available online at 203.190.147.148/evole2circos/